A computational modelling approach combined with cellular electrophysiology data provides insights into the therapeutic benefit of targeting the late Na+ current. (15th March 2015) - Yang, Pei‐Chi; Song, Yejia; Giles, Wayne R.; Horvath, Balazs; Chen‐Izu, Ye; Belardinelli, Luiz; Rajamani, Sridharan; Clancy, Colleen E.
<x xml:space="preserve">Abstract</x> Key points The ventricular action potential plateau is a phase of high resistance, which makes ventricular myocytes vulnerable to small electrical perturbations. We developed a computationally based model of GS‐458967 interaction with the cardiac Na+ channel, informed by experimental data recorded from guinea pig isolated single ventricular myocytes. The model predicts that the therapeutic potential of GS‐458967 derives largely from the designed property of significant potent selectivity for INaL. Abstract Selective inhibition of the slowly inactivating or late Na+ current (INaL) in patients with inherited or acquired arrhythmia syndrome may confer therapeutic benefit by reducing the incidence of triggers for arrhythmia and suppressing one component of arrhythmia‐promoting cardiac substrates (e.g. prolonged refractoriness and spatiotemporal dispersion of action potential duration). Recently, a novel compound that preferentially and potently reduces INaL, GS‐458967 (IC50 for block of INaL = 130 nm) has been studied. Experimental measurements of the effects of GS‐458967 on endogenous INaL in guinea pig ventricular myocytes demonstrate a robust concentration‐dependent reduction in action potential duration (APD). Using experimental data to calibrate INaL and the rapidly activating delayed rectifier K+ current, IKr, in the Faber–Rudy computationally based model of the guinea pig ventricular action potential, we simulated effects of GS‐458967 on guinea pig ventricular APD. GS‐458967 (0.1 μm) caused a 28.67% block of INaL and 12.57% APD shortening in experiments, while the model predicted 10.06% APD shortening with 29.33% block of INaL. An additional effect of INaL block is to reduce the time during which the membrane potential is in a high resistance state (i.e. the action potential plateau). To test the hypothesis that targeted block of INaL would make ventricular myocytes less susceptible to small electrical perturbations, we used the computational model to test the degree of APD prolongation induced by small electrical perturbations in normal cells and in cells with simulated long QT syndrome. The model predicted a substantial dose‐dependent reduction in sensitivity to small electrical perturbations as evidenced by action potential duration at 90% repolarization variability in the presence of GS‐458967‐induced INaL block. This effect was especially potent in the 'disease setting' of inherited long QT syndrome. Using a combined experimental and theoretical approach, our results suggest that INaL block is a potent therapeutic strategy. This is because reduction of INaL stabilizes the action potential waveform by reducing depolarizing current during the plateau phase of the action potential. This reduces the most vulnerable phase of the action potential with high membrane resistance. In summary, by reducing the sensitivity of the myocardial substrate to small electrical perturbations that promote arrhythmia triggers, agents such as GS‐458967 may constitute an effective antiarrhythmic pharmacological strategy.